Pengantar hukum Islam - T.M. Hasbi Ash-Shiddieqy (Bulan Bintang, 1980)
Oen, Jil. 1=c.1-2; Jil.2=c.1?oen, jil.1=c.3-5; Jil.2=c.2/ir, jil.1,c.6-7/tr, jil.1=c.8-10; jil.2=c.3-5/en, jil.2=c.6/tr, jil.1=11/en, jil.2=c.7/an, jil.1=c.12/ast jil.1 =c.12/en, jil.1=c21